Relationship between overall diet quality and composition and diarrhea in American adults: a cross-sectional study - Wu, Jincheng; Lin, Xiaomin; Zeng, Qingfeng; Zeng, Xianghui; Cao, Gang; Xie, Muchu; Luo, Jianping; Li, Lihua; Zeng, Guiping; Liu, Shili (Frontiers in Nutrition, 2025)
BackgroundDiarrhea, as a significant aspect of digestive system disorders, the relationship between dietary quality and gut health has attracted increasing attention. This study aims to investigate the association between the Healthy Eating Index 2015 and its components and the risk of diarrhea.MethodsThis study data from the 2007 to 2010 National Health and Nutrition Examination Survey databases, which included 7,395 adult participants. Diarrhea was defined according to the Bristol Stool Form Scale (BSFS) from the Gut Health Questionnaire. The HEI-2015 score was estimated based on two 24-h dietary recall interviews. surveylogistic regression models were employed to examine the association between the HEI-2015 and its components and the risk of diarrhea.ResultsThe results of this study indicated that, the HEI-2015 was significantly associated with a reduced risk of diarrhea. Specifically, a 1-point increase in the HEI-2015 score was associated with a 1% decrease in the odds of diarrhea (OR:0.99, 95% CI:0.98–0.99). A 1-point increase in the whole grain score was linked to a 5% reduction in the odds of diarrhea (OR:0.95, 95% CI:0.91–0.99), while a 1-point increase in the refined grain score was associated with a 3% reduction in the odds of diarrhea (OR:0.97, 95% CI:0.94–0.99).ConclusionThis study adds further evidence to the health benefits of whole grains and the potential risks associated with refined grains. As part of a balanced diet, promoting whole grain consumption could have a significant impact on public health by reducing the incidence of diarrhea and improving overall well-being.